COVID-19’s effect on healthcare disparities: delivery, reimbursement, and premature mortality in residentially segregated populations - Feras, Kasabji; Vincze, Ferenc; Lakatos, Kinga; Pálinkás, Anita; Kőrösi, László; Ulicska, László; Kósa, Karolina; Sándor, János (Frontiers in Public Health, 2025)
IntroductionSpatially segregated, socio-economically deprived communities often face significant health disparities. This paper evaluates the impact of COVID-19 on healthcare delivery and reimbursement disparities in Hungary, particularly focusing on segregated populations.AimsTo examine healthcare utilization and reimbursement patterns among patients in segregated areas (SA) and non-segregated or complementary areas (CA) during the first year of the COVID-19 pandemic, compared to pre-pandemic levels, and to understand how these patterns influenced overall health outcomes.MethodsA cross-sectional study using 2019 and 2020 healthcare data from all Hungarian general medical practices (GMPs) was conducted. Segregated areas were identified based on governmental criteria, and healthcare indicators were standardized by age, sex, and socioeconomic status. Key indicators included General Practitioner (GP) visits, outpatient services, Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) usage, hospitalizations, healthcare reimbursement, and premature mortality.ResultsIn 2020, there was a notable reduction in healthcare services utilization due to COVID-19 restrictions, with GP visits declining by 10.43% in SAs and 4.13% in CAs. Outpatient services decreased by 19.16% in SAs and 12.45% in CAs, while hospitalizations dropped by over 23.52%. Despite these reductions, the relative risk (RR) of healthcare service use remained higher in SAs compared to CAs (RR = 1.22, 95% CI: 1.219;1.223). Healthcare reimbursement was significantly lower in SAs (RR = 0.940, 95% CI: 0.929;0.951), and premature mortality was higher (RR = 1.184, 95% CI: 1.087;1.289).ConclusionThe COVID-19 pandemic led to a significant reduction in healthcare utilization across Hungary. However, segregated populations in 2020 continued to have higher healthcare service use but received lower reimbursement, indicating persistent healthcare disparities. The consistently higher premature mortality rate in SAs underscores the need for targeted interventions and improved healthcare access and quality for vulnerable communities. Future policies should be built on data from comprehensive monitoring systems to address and mitigate these disparities, ensuring equitable healthcare access in and out of health crises.